Clinical Indications of Asanadi Kwatha A Scientific and Experiential View - Acharya G, Shripathi; Acharya, Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2022)
Asanadi kwatha in asavarishta base is widely used by Ayurveda physicians . It contains pittahara and kashaya rasayukta drugs. It is used mainly in diabetes mellitus , raktaja vikaras and disorders of anorectal region . In disorders like diabetes mellitus , chronic non healing ulcer, hemorrhoids , fistula in ano, chronic non healing ulcer, various skin disorders and pittaja vyadhis . It is Kashaya Rasayukta , Sheetavirya , Pittahara And Raktashodhaka in action . Actions like Raktashodhaka , Kandughna, Virechana , Malavatanulomana , Pittahara , Dahahara, Kushthaghna, Rasayana And Dipana are seen in this formulation . In this paper, clinical indications of Asanadi kwatha is explained in a scientific and experiential view.